Dental pain and its impact on quality of life among indigenous adolescents of Himalayas (Ladakh), India - Kuldeep Singh Shekhawat; Arunima Chauhan; Marie Nordstroem (Wolters Kluwer Medknow Publications, 2016)
Background: Ladakh has less than optimal oral health care services and a poor transport and connectivity with other areas of the country during most part of the year. Therefore, immediate address to any dental pain is not possible. This study aims to determine the prevalence of dental pain among 12-15-year-old schoolchildren of Leh, Ladakh after the commutation impairing time of the year. Materials and Methods: A cross-sectional study was conducted in May 2014 to determine the prevalence and impact of dental pain among adolescents residing in Leh, Ladakh. A total of 264 students in the age group of 12-15 years participated in the study. The data were obtained using a pretested questionnaire that elicited information on past experience (6 months) of dental pain and the resultant impact on their daily lives. Statistical Analysis Used: Descriptive statistics was used for distribution of frequencies. Results: The response rate was 75.7%. Seventy-seven percent of the students reported dental pain in the past 6 months. About 89% of the students reported, at least, one impact due to dental pain. Females reported more than their male counterpart. Difficulty in eating was found to be commonly reported impact followed by difficulty in sleeping. Conclusions: The prevalence of dental pain and its impact was found to be high. There is a need for a paradigm shift in focus of oral health services from urban areas to remote and rural areas. Knowledge about the magnitude of dental pain can be used to evaluate and plan preventive and curative services in remote and rural areas.